Predictors and Mortality for Worsening Left Ventricular Ejection Fraction in Patients With HFpEF - Chen, Liling; Huang, Zhidong; Zhao, Xiaoli; Liang, Jingjing; Lu, Xiaozhao; He, Yibo; Kang, Yu; Xie, Yun; Liu, Jin; Liu, Yong; Yang, Jin; Yu, Weixu; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Definitions of declined Left ventricular ejection fraction (LVEF) varied, and the results of previous studies concerning the association of mortality with declined LVEF were inconsistent. Our study was designed to comprehensively assess the early declined LVEF and its impact on mortality. Methods and Results: 1418 consecutive HFpEF patients with LVEF re-measurement were included from Cardiorenal ImprovemeNt Registry. Worsening LVEF was defined as a ≥5% absolutely decline from baseline LVEF within 3 to 12 months after discharge. Cox and Logistic regression analyses were performed to assess prognostic effect and predictors for worsening LVEF, respectively. Among all HFpEF patients included in the final analysis, 457 (32.2%) occurred worsening LVEF. During a median follow-up of 3.2 years (interquartile range: 2.3–4.0 years), 92 (6.5%) patients died. HFpEF patients with worsening LVEF have a higher mortality relative to those without (9.2% vs. 5.2%, adjusted hazard ratio [aHR]: 2.18, 95% confidence interval [CI]: 1.35-3.52). In multivariable logistical models, larger left ventricular end-diastolic dimension (LVEDD) and lower high-density lipoprotein cholesterol (HDL-C) emerged as predict factors of worsening LVEF. Conclusions: One out of three individuals with HFpEF occurr worsening LVEF, which is associated with 2.2-fold increased mortality. Larger LVEDD and lower HDL-C at baseline can predict worsening LVEF. Further studies are needed to prospectively assess the efficacy of cardiac structure and function related management on outcomes in HFpEF.